Current status of prognostic factors in patients with metastatic renal cell carcinoma. (8th April 2019) - Teishima, Jun; Inoue, Shogo; Hayashi, Tetsutaro; Matsubara, Akio
Abstract: In recent years, the induction of novel agents, including molecular‐targeted agents and immune checkpoint inhibitors, have dramatically changed therapeutic options and their outcomes for metastatic renal cell carcinoma. Several prognostic models based on the data of patients with metastatic renal cell carcinoma treated with targeted agents or cytokine therapy have been useful in real clinical practice. Serum or peripheral blood markers related to inflammatory response have been reported to be associated with their prognosis or therapeutic efficacy. In addition to them, investigation for novel predictive factors that represent the efficacy of agents, the risk of adverse events and the prognosis are required for the advance of therapeutic strategies. The present review discusses the conventional prognostic models and clinical factors, and recent advances of the identification of some of the most promising molecules as novel biomarkers for metastatic renal cell carcinoma.